Physicochemical And Sensory Properties Of Surimi-Like Material From Duck Meat And Its Application In Burger - Ramadhan, Kurnia (2012)
This study was carried out to determine: the effect of two numbers of washing cycle (twice and thrice washings) and four types of washing solutions (tap water, NaCl, NaHCO3, and sodium phosphate buffer) on composition, functional properties, and microstructure of surimi-like material made from duck meat (DSLM); the cryoprotective activity of four types of low sweetness cryoprotectants (polydextrose, trehalose, lactitol, and palatinit), compared to commercial blend cryoprotectant (sucrose-sorbitol) and control on DSLM during frozen storage and exposed to freeze-thaw cycles; and the physicochemical, textural and sensory properties burgers made from DSLM (added with polydextrose and sucrose-sorbitol blend) and compared to burgers made from chicken and duck meat. Three times washing on duck meat was sufficient to remove the undesirable components in surimi-like material such as fats and sarcoplasmic proteins, to concentrate the myofibrillar proteins, to form a compact and dense structure of cooked gel which resulted in high values of functional and textural properties. Among the washing solutions tested, washing with tap water achieved the highest gel strength, hardness, cohesiveness, and chewiness significantly; moderate increases in water holding capacity (WHC), pH, protein solubility, lightness, and whiteness; and left a small amount of fat.